Antecedents and Impacts of E-Business Aligment Amongst Small and Medium-Sized Enterprises - Rosli, Mohamad (2012)
E-business has great potentials for firms to extend their business efficiency. Nevertheless, due to various problems and constraints, the e-business deployment within SMEs sector has been reported as not effective. To ensure effective e-business deployment, necessary measures are needed to assess how firms align diverse ebusiness capabilities in support of their business operation. This study therefore aims to investigate the extent firms align diverse e-business capabilities across business processes (e-business alignment). Using a strategic fit perspective, this study has observed two major propositions. First, firms‟ ability to align e-business to support the most crucial business processes has potentially led to better realisation of ebusiness values. Secondly, certain managerial and environmental conditions have explained the differing characteristics of e-business alignment amongst firms. This study employs quantitative research approach using survey method to collect and collate evidences from 140 owner/managers of SMEs. Preliminary analysis has indicated e-business alignment/misalignment patterns across business functions. The cluster analysis further reveals three distinct profiles with different characteristics of e-business alignment. These profiles are labelled as 'highly fit', 'moderately fit' and 'low fit' based on their e-business fit characteristics. This result confirms the first proposition where highly aligned firms will report greater and wider e-business impacts. The second proposition reveals that environmental uncertainty, IT sophistication, owner/manager knowledge on advanced IT/IS, e-business deployment status, and support network are significant predictors to different e-business alignment characteristics among firms. This study suggests that firms relatively have different priority over e-business solutions to support their business. These findings have demonstrated why some firms do not progress to a higher e-business ladder. It further justifies unequal deployment of e-business solutions to support functions across firms.